Legal Issues Raised By the Democratization of Cryptography: Challenges and Enforcement of Export Control Regimes in a Globalized World (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Export controls imposed on cryptographic softwareaffect the possibilities of individuals and companies of lawfully obtainingcryptographic software, in order to protect themselves against breaches ofsecurity.  On the other hand, exportcontrol regimes constantly face new challenges from non- lawabiding people, whoseek to discover new ways and means to circumvent controls. The inherentlyglobal nature of information and communication networks makes the task ofexport control enforcement quite difficult and the difficulties of defining andenforcing jurisdictional boundaries in the international environment becomemore and more evident.